Chinese Investments in Africa: What Have We Learnt? - Abodohoui, Alexis; Su, Zhan; Da-Silva, Imelda (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
With this systematic review, we intend to achieve three aims: (1) to take an inventory of what have been done so far in the field of Chinese investments in Africa; (2) to critically analyze the actors, motivations, mode of entry, impacts and management challenges, in the light of international business theories; and (3) to identify research gaps for what needs to be done in the future. Based on different international business theories, this review offers new insights to explore Chinese investments in African countries and contribute to the overall body of knowledge about Sino-Africa relationship.